(untitled) (Homiletic, 2015)
The essays that follow were first presented as part of a consultation on preaching and postcolonial theology at Boston University in October, 2014, sponsored by the BU Center for Practical Theology. The consultation was an opportunity to bring together a leading scholar in postcolonial theology, Dr. Kwok Pui-lan of Episcopal Theological Seminary; two homileticians who have already started to grapple with postcolonial theory and theology in their work, Drs. Pablo Jiménez and Sarah Travis; and two Ph.D. students, Revs. Tim Jones and Lis Valle, from BU and Vanderbilt respectively. The goal of this interdisciplinary consultation was to jump start a wider conversation on today’s postcolonial context in North American homiletics for the sake of the practice of preaching. As an ad hoc research team for the fall term of 2014, we editors named above were all pleased to help bring this consultation together and are now excited to bring its fruits to you, the international and diverse body of homileticians based in North America, the Academy of Homiletics. *Note: Special thanks go to Drs. Shelly Rambo, Cristian De La Rosa, and Sung Jung Oh, who together with Revs. Yohan Go and Duse Lee, responded to the papers at the consultation in October, 2014. Their responses were crucial in the process of revising these papers for publication.